Strategic management :text & cases (BMS 2nd year 3rd semester) - Bobade Anita (Vipul Prakashan,Mumbai, 2009)
B.M.S.
ENGLISH
Keywords: Strategic management :text & cases (BMS 2nd year 3rd semester); B.M.S.; B.M.S.